Boosting Students’ Mufradat Competence through the Read and Find! Learning Media - Friska Dwi Apriliani; Muflihah Muflihah (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
Mastery of mufradat (vocabulary) is a fundamental foundation in learning Arabic. However, the learning conditions at MTsN 2 Lamongan indicate that seventh-grade students still demonstrate low vocabulary mastery, which is influenced by the predominance of conventional teaching methods and the limited use of instructional media. This study aims to describe the implementation and effectiveness of the manual media Read & Find! in improving students’ Arabic vocabulary mastery. The research employed a descriptive qualitative approach, with data collected through participatory observation, semi-structured interviews, and document analysis. The findings reveal that the Read & Find! media, in the form of picture–word matching cards, is able to create a more interactive and enjoyable learning environment. The media facilitates visual–verbal associations, enabling students to recognize, remember, and understand vocabulary more effectively. Students also demonstrated increased participation, confidence, and accuracy in matching vocabulary with the appropriate images. These findings imply that the use of simple visual media such as Read & Find! can serve as an effective and practical instructional strategy for Arabic teachers to enhance vocabulary mastery and to promote more interactive and student-centered learning.